2011
DOI: 10.19030/jber.v7i2.2262
|View full text |Cite
|
Sign up to set email alerts
|

Fraud Risk Factor Of The Fraud Triangle Assessing The Likelihood Of Fraudulent Financial Reporting

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
110
7
25

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(178 citation statements)
references
References 59 publications
16
110
7
25
Order By: Relevance
“…In the past, much opportunity is possible for employees to commit white collar crimes if internal control of the management is low (Kassem & Higson, 2012;Wolfe & Hermanson, 2004). Previous studies (Dinapoli, 2008;Omar & Din, 2010;Lou &Wang, 2011, andDellaportas, 2013) have indicated that various elements, such as unclear separation of roles and responsibilities, poor documentation on policies, procedures and guidelines, insufficient physical controls by security guards, entering the transaction in an untimely manner, unrestricted access to corporate check books, and insecure control of cash boxes, present numerous opportunities for fraud to occur within the banking sector. Thus, management should emphasize on policy implementation and strengthen the power of internal control.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, much opportunity is possible for employees to commit white collar crimes if internal control of the management is low (Kassem & Higson, 2012;Wolfe & Hermanson, 2004). Previous studies (Dinapoli, 2008;Omar & Din, 2010;Lou &Wang, 2011, andDellaportas, 2013) have indicated that various elements, such as unclear separation of roles and responsibilities, poor documentation on policies, procedures and guidelines, insufficient physical controls by security guards, entering the transaction in an untimely manner, unrestricted access to corporate check books, and insecure control of cash boxes, present numerous opportunities for fraud to occur within the banking sector. Thus, management should emphasize on policy implementation and strengthen the power of internal control.…”
Section: Discussionmentioning
confidence: 99%
“…First, Financial Target, done by (Ansar, 2012;Fimanaya and Syafruddin, 2014;Lou and Wang, 2009;Rahmanti and Daljono, 2013) where their research results showed the significant effect towards accounting fraud. Second, ineffective monitoring, done by (Antonia, 2008;Skousen, Smith and Wright, 2009) their research results showed the significant effect towards accounting fraud.…”
Section: Introductionmentioning
confidence: 99%
“…Lou and Wang (2009) found that complex transactions are accompanied by a high inherent risk due to the involvement of a high degree of management judgment and subjectivity.…”
Section: Independent Variablesmentioning
confidence: 99%
“…ese studies include those that investigate the probability of occurrence of accounting and corporate fraud, such as those by Beasley (1996), Brazel, Jones, andZimbelman (2009), Crutcheley, Jensen andMarshall (2007), Erickson, Halon and Maydew (2006), Lou and Wang (2009), Troy, Smith, and Domino (2011), and Wang et al (2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation